Mechanical model and verification of tillage layer compaction considering the operating dynamics of heavy tractor units - Yang, Xiao; Hu, Hongrui; Liu, Xianglei; Huang, Junhao; Li, Wenjie (International Journal of Agricultural and Biological Engineering, 2025)
Plowing operations can improve the quality of the shallow soil layer, but plowing tractors still cause compaction effects on the deeper soil layers. The temporal and spatial accumulation of compaction effects can hinder crop growth, thereby reducing the overall efficiency of plowing operations and creating obstacles to soil ecological health. It is urgent to address the bottlenecks in mechanized ecological operations. This paper addresses the unclear mechanical effects of heavy-duty tractor tillage equipment on soil compaction in the tillage layer. By integrating and constructing a ‘‘heavy-duty tractor-tillage layer soil’’ system dynamics coupling model, it identifies the primary influencing factors of joint tillage operations on soil compaction in the tillage layer and explores the response patterns of tillage equipment parameters to the soil compaction process. The research results indicate that as the number of compaction operations increases, soil compaction increases, and soil stress transmission shows a gradually decreasing trend; when the tillage unit’s operating speed is 3 km/h, the soil stress at a depth of 10 cm can reach a maximum of 499.2 kPa; when the operating speed is 6 km/h, the soil stress at a depth of 10 cm reaches a maximum of 469.1 kPa; when the operating speed is 9 km/h, the soil stress at a depth of 10 cm reaches a maximum of 438.8 kPa; when the acceleration and longitudinal acceleration increase, soil stress correspondingly increases; when the direction of lateral acceleration changes, the center of gravity of the tractor shifts, and the trends in soil stress on the inner and outer sides of the tires are opposite. The research findings can provide theoretical references for improving the operational efficiency of the unit and the development of black soil protection and utilization technologies. Keywords: heavy-duty wheeled tractor, tillage compaction mechanism, impact of crew operations, mechanical ecology, black earth conservation DOI: 10.25165/j.ijabe.20251805.9372 Citation: Yang X, Hu H R, Liu X L, Huang J H, Li W J. Mechanical model and verification of tillage layer compaction considering the operating dynamics of heavy tractor units. Int J Agric & Biol Eng, 2025; 18(5): 154–164.